The effect of online CPR training on the knowledge and practice of the Red Crescent Student Association Volunteers during the COVID‐19 pandemic: A randomized clinical trial study - Mohammad Salehpoor-Emran; Shahzad Pashaeypoor; Zahra Amrollah Majdabadi; Bernd W. Böttiger; Sarieh Poortaghi; Shima Haghani (Resuscitation Plus, 2025)
Background: The propagation of basic cardiopulmonary resuscitation (CPR) training can increase patient survival and reduce brain injury; however, the conventional educational approach has shifted towards e-learning during the COVID-19 pandemic. Therefore, this study aimed to determine the effect of online CPR training on the knowledge and performance of the Red Crescent Student Association Volunteers. Methods: A randomized controlled trial was conducted on 70 Red Crescent Student Association Volunteers. The participants were allocated to intervention and control groups using a simple random allocation method. The primary study outcomes were measured using a validated knowledge assessment and a CPR performance checklist, both validated according to the 2020 American Heart Association (AHA) guidelines. These tools were administered to all participants before and one month after the intervention. The intervention group received one-hour online training sessions per day over three days. The educational content, including the topics related to basic adult CPR training, was formulated according to the 2020 AHA guidelines; however, the control group didn’t receive any online educational program. The collected data were analyzed using the SPSS16 software at a significance level of P < 0.05. Results: There was no significant difference in demographic variables between the two groups (P > 0.05). Also, after online CPR training, the mean scores of the knowledge (9.84 ± 1.88 vs. 7.94 ± 2.17; P = 0.009; effect size = 0.104) and the practice (31.38 ± 6.98 vs. 20.58 ± 7.20; P < 0.001; effect size = 0.345) were significantly higher in the intervention group compared to the control group. Conclusion: Booster CPR training with e-learning was associated with improved knowledge and practice of the Red Crescent Student Association Volunteers. Therefore, this method may be considered as a supplementary training approach, especially in emergencies like emerging pandemics, where traditional training methods are limited.